Grinding Media Evaluation at Brunswick Mining (f15a982e-65ba-4a8c-a10b-05d2c80d3be9) - R. Grant; R. Tessier; C. Bazin (Canadian Institute of Mining, Metallurgy and Petroleum, 1993)
"Brunswick Mining has investigated grinding media optimization for the purpose of improving the flotation feed and regrind product size distributions to enhance metal recoveries. The paper presents findings in the on-going testing of various sizes and shapes of grinding media. Breakage rates are used as an aid to assess the effect of grinding media. Results of empirical and phenomenological analyses demonstrate the importance of adequate selection of media sizes on the milling operation.INTRODUCTIONBrunswick Mining and Smelting operates one of the world's largest lead and zinc mine near Bathurst, New-Brunswick. The No. 12 ore body is an extremely fine grained volcanogenic massive lead, zinc, copper, silver, iron sulphide body between two metamorphosed sedimentary and felsic volcanic rock units. Pyrite content is about 60% with 20% non-sulphide minerals, mainly silica and chlorite. The operation is currently processing 10,500 tonnes of ore per day in conventional crushing, grinding, differential flotation and dewatering circuits. Details on the circuit can be found elsewhere (e.g. Hendriks and Ounpuu, 1985; Grant et al., 1991).The mill has operated for more than 25 years and despite the past milling experience, there has been much disagreement as to the required grind size. Since 1964, fineness of the flotation feed ranged from 60% to 80% passing 400 mesh (37µm) and averaged slightly over 71%in1992. Results from mineralogical analysis (Petruk and Schnarr,1981; Coleman, 1988), Brunswick metallurgical laboratory (Grant et al., 1991; Shannon et al., 1992) and Lakefield pilot plant tests (Hendriks, 1984; Hendriks and Ounpuu, 1985) clearly indicate that improved metal recoveries can be achieved by an increase in the fineness of grind, and more specifically by maximizing the amount of material in the 15-25µm range."